2018
DOI: 10.1515/cclm-2018-1065
|View full text |Cite
|
Sign up to set email alerts
|

A novel machine learning-derived decision tree including uPA/PAI-1 for breast cancer care

Abstract: Background uPA and PAI-1 are breast cancer biomarkers that evaluate the benefit of chemotherapy (CT) for HER2-negative, estrogen receptor-positive, low or intermediate grade patients. Our objectives were to observe clinical routine use of uPA/PAI-1 and to build a new therapeutic decision tree integrating uPA/PAI-1. Methods We observed the concordance between CT indications proposed by a canonical decision tree representative of French practices (not including uPA/PAI-1) and actual CT prescriptions decided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…uPA/PAI-1 is used together with other biomarkers in routine clinical practice, guiding the therapeutic choice, but, so far, uPA/PAI-1 is not considered sufficient to replace established parameters in clinical practice [128]. Uhl et al [125] showed that heteromerization of uPA and PAI-1 attracts neutrophils to cancerous lesions, thereby supporting tumor growth and metastasis.…”
Section: Upa/pai-1mentioning
confidence: 99%
“…uPA/PAI-1 is used together with other biomarkers in routine clinical practice, guiding the therapeutic choice, but, so far, uPA/PAI-1 is not considered sufficient to replace established parameters in clinical practice [128]. Uhl et al [125] showed that heteromerization of uPA and PAI-1 attracts neutrophils to cancerous lesions, thereby supporting tumor growth and metastasis.…”
Section: Upa/pai-1mentioning
confidence: 99%
“…1) Decision tree algorithm is to construct a suitable decision tree by learning the source data [40]. The decision tree generation is mainly divided into the flowing two steps, which are usually achieved by learning the labeled samples: (a) Node splitting: in general, when the attribute represented by a node cannot be judged, the node is divided into two.…”
Section: ) Tree and Forestmentioning
confidence: 99%
“…Different from kernel-based method, tree and forest method are a summary of expert experience, which are widely used in practical application [44]. For example, Reix et al [40] built a new canonical decision tree model to analysis concordant and non-concordant CT prescriptions and find the decisive factor for breast cancer care. To provide a low-cost sensing strategy for air quality monitoring, Zimmerman et al [60] used random forests to design a comprehensive machine learning calibration model, and this model performed well on real-time air monitoring.…”
Section: Introductionmentioning
confidence: 99%